YIELD ATTRIBUTES TTRIBUTES, YIELD AND QUALITY OF BLACK GREENGRAM ( GREENGRAM (VIGNA RADIATA L.) AS INFLUENCED BY ORGANIC MANURES ANIC MANURES, BIOFERTILIZER AND PHOSPHORUS TILIZER AND PHOSPHORUS FERTILIZATION - J. D. THANKI, S. N. CHAUDHARI; CHAUDHARI, V. D. (The Bioscan, 2015)
A field experiment was conducted during rabi season of 2013-14 at College Farm, Navsari Agricultural University, Navsari to study “Effect of organic manures, biofertilizer and phosphorus fertilization on growth, yield and quality of black greengram(Vignaradiata(L.) under south Gujarat condition”. Among different organic manures, biocompost 2 t/ha (M2 ) rightly dominated and established its superiority in respect to almost all yield attributes. Application of biocompost 2 t/ha (M2) produced significantly highest seed 909 kg/ha) and straw (1771.56 kg/ha) yields over other treatments. The percent increase in seed yield with application of biocom post 2 t/ha over FYM 4 t/ha and control were 7.63 and 23.75 respectively. Crop fertilized with biocompost 2 t/ha recorded significantly highest protein content and protein yield as compared to control. Significantly the highest seed (830.36 kg/ha) and straw (1607.70 kg/ha) yields were recorded with PSB inoculation. Seed and straw yields as well as yield attributes and quality of black greengram were significantly influenced by phosphorus application. In most of characters, Application of 40 kgP2 O5 /ha showed its superiority over control. Significantly the highest seed (852.42 kg/ha) and straw (1670.5 kg/ha) yields were recorded with application of 40 kg P2O5/ha over control.